Leadership - Davut Göker, Suleyman (IntechOpen, 2018)
This book, when compared to other books on leadership, is expected to present a new understanding of the essential features of leadership and it varies from the wealth of literature in the following ways: firstly, this book attempts to include leaders at all management levels within an organization and across various sectors. This book also aims to provide experiences and reflections across a variety of sectors and organizational structures rather than focusing on one set of definitions (as is the case in current leadership sources). Finally, this book is expected to offer a new perspective addressing and inspiring actual leaders today and potential ones and contributing to the existing debate on leadership.